1996
DOI: 10.1111/j.1460-9568.1996.tb01221.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repeated Sensory Stimulation (Electro‐acupuncture) and Physical Exercise (Running) on Open‐field Behaviour and Concentrations of Neuropeptides in the Hippocampus in WKY and SHR rats

Abstract: The effects of repeated sensory stimulation (electro-acupuncture) and physical exercise (running) on open-field behaviour and on hippocampal concentrations of neuropeptide Y, neurokinin A, substance P, galanin and vasoactive intestinal peptide (VIP)-like immunoreactivities were studied in WKY (wistar-Kyoto) and SHR (spontaneously hypertensive) rats. Significantly higher concentrations of substance P-like immunoreactivity, neurokinin A-like immunoreactivity and neuropeptide Y-like immunoreactivity were found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…NO has been suggested to mitigate the cerebral vasospasm [37]. EA plus running could increase the levels of neuropeptide Y, neurokinin A, and substance P in the hippocampus [38]. Neuropeptide Y can enhance neurogenesis [39], neurokinin A and substance P have been reported to initiate angiogenesis, and neurokinin A could also regulate the vascular tone and blood flow [40].…”
Section: The Potential Of Acupuncture For Secondary Prevention Of Strmentioning
confidence: 99%
“…NO has been suggested to mitigate the cerebral vasospasm [37]. EA plus running could increase the levels of neuropeptide Y, neurokinin A, and substance P in the hippocampus [38]. Neuropeptide Y can enhance neurogenesis [39], neurokinin A and substance P have been reported to initiate angiogenesis, and neurokinin A could also regulate the vascular tone and blood flow [40].…”
Section: The Potential Of Acupuncture For Secondary Prevention Of Strmentioning
confidence: 99%
“…Bucinskaite et al have previously reported on the effects of repeated electroacupuncture treatments on open-field behaviour and on hippocampal concentrations of neuropeptide Y (NPY), neurokinin A (NKA), substance P (SP), galanin (GAL) and vasoactive intestinal peptide (VIP)-like immunoreactivities (-LI) in Wistar-Kyoto (WKY) and spontaneously hypertensive rats (SHR). 6 Significantly higher concentrations of SP-LI, NKA-LI and NPY-LI were found in the hippocampus immediately after three weeks of electroacupuncture treatment. Changes in neuropeptide concentrations were similar in the two rat strains.…”
mentioning
confidence: 99%
“…Bucinskaite Education, practice and debate in the two rat strains Wistar-Kyoto (WKY) and spontaneously hypertensive rats (SHR). 84 Significantly higher concentrations of SP-LI, NKA-LI and NPY-LI were found in the hippocampus immediately after three weeks of electroacupuncture treatment compared to untreated animals with similar changes in neuropeptide concentrations in the two rat strains. Open-field behaviour was significantly reduced during the treatment period in both strains.…”
Section: Acupuncture Reward and Neuromodulationmentioning
confidence: 89%